Death, the environment, and theology. Issue 4 (5th December 2018) - Pihkala, Panu
Abstract: In order to fare better amidst a growing environmental crisis, we need to face death and mortality in more profound ways. Recent psychosocial research on environmental themes has provided crucial insights. People have trouble dealing with mortality, and because environmental threats remind them (often unconsciously) of death, they tend to escape into non‐sustainable behavior. In this article, I present key insights from this interdisciplinary research and explore its relevance for practicing theologians.